Batik Dermayon: Expression of Femininity in North Coast of Java - Prawira, Nanang Ganda; Putri Hk, Aditya Aditama (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
To date, Javanese-Indonesian coastal women have only been part of the batik craft industry, but their strategic roles and expressions have never been disclosed or cared. Whereas the feminine side and the aesthetic symbolic adaptation of Batik-crafter women are very important issues in the creation of the Indonesian cultural repertoire. This study succeeded in explaining the visual identity signs and aesthetic structures described by the community of the crafter woman in the Paoman Village, as well as revealing the meaning of the Indramayu written batik motif as a sign in coastal culture.